THE LEXICONS OF ANIMAL CLASSIFICATION IN JAVANESE: A COGNITIVE SEMANTICS APPROACH - Danang Satria Nugraha (Sanata Dharma University, 2019)
This study aimed to describe the lexicons of animal classification in Javanese. The classification refers to a categorization system based on the semantic aspects of naming constructions. Through a combination of observation method (or simak method) based on Blommaerts model (2013), constructions such as mendha, pitik kampung, and celeng collected from the use of Javanese both oral and written. Based on semantical analysis techniques, the data are analyzed in line with the use of padan method and interpreted based on Durantis theory (2004). The results of the analysis are presented in description along with the classification chart. In general, the lexicons in animal classification can be devided into, at least, five classifications, namely classification (a) ingon-ingonan, (b) alasan, (c) satoan, (d) buron, and (e) pangirid. In accordance with the world view of Javanese speakers, there are three wisdom presented in the animal classification, namely (a) ora mateni sakabehe do not kill every living thing, (b) ora ngrusak sakabehe do not broke anything, and (c) ora mangan kewan do not meal the specific animals. For further study, the contrastive analysis on lexicons of plants and animals classification in Javanese, espcially in farming register, is the interesting research topic in the light of Cognitive Semantics.